PERAN KERJASAMA EUROPEAN DOWN SYNDROME ASSOCIATION (EDSA) DAN DEUTCHES DOWN SYNDROME INFOCENTER (DS-InfoCenter) DALAM MENINGKATKAN KUALITAS HIDUP PENYANDANG DOWN SYNDROME DI JERMAN - Putri Rahma Dewi; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aims to know the role within cooperation between EDSA or also called the European Down Syndrome Association with DS-InfoCenter or Deutches Down Syndrome Info Center and how is this cooperation giving an impact to the quality of life for Down Syndrome carrier in Germany. The research method used in this research is descriptive qualitative method with constructivist perspective. In the process of collecting research data, the author uses direct observation as well as live interviews conducted on site and documentary studies obtained from printed media such as books and journals, as well as online media such as sites and videos. Through research conducted and data processing conducted by the authors, there are 3 roles produced by EDSA and DS-Infocenter in improving the quality of life of people with down syndrome in Germany. As an instrument, EDSA works closely with Ds-infocenter in terms of facilities. As an arena, EDSA and Ds-infocenter became a forum for expert meetings. And as an independent actor, EDSA has the power to conduct a program without third-party interference.Keyword: Down Syndrome, EDSA, DS-InfoCenter, Clinical Conditions, Quality of Life